Comparative study on the extraction of β-carotene in the flesh and peel of papaya - Mohd Razman, Fadzil (2010)
The objective of this study was to compare and optimise the extraction conditions for Î²carotene compounds from flesh and peel of papaya (Carica papaya) using extraction process and HPLC analysis also to determine mineral content and microbe affected. Extraction is a process to obtaining something from mixture or compound by chemical or physical methods. Liquid-liquid extraction is used to extract and purify carotenoids from flesh and peel of Papaya and then this sample will be analysis in High Performance Liquid Chromatographer (HPLC).Several parameter was applied to determine the effects of acetone as a solvent, acetone ratio/ concentration (%), extraction temperature (Â°C), and extraction time (minutes) on Î²-carotene content from flesh and peel of papaya (Carica papaya). The independent variables were coded at five levels and their actual values were selected based on the results of single factor experiments. Results showed that acetone concentration was the most significant factor affecting the concentration of Î²-carotene. The optimum extraction conditions were found to be acetone concentration of 60%, extraction temperature of 40Â°C, and extraction time of 60 minutes. Under the optimised conditions, the experimental value for Î²-carotene content was (3.45x10-5mg/L) for peel and (3.01x10-5) mg/L for flesh of papaya